Divergent immediate and delayed effects of juvenile exposure to doxorubicin on the thymus in C57BL/6 mice - Benu George; Korbyn J. V. Dahlquist; Marianne K. O. Grant; Mary R. Daniel; Declan M. Smith; Ian Ahlberg; Karim T. Sadak; Davis Seelig; Christina D. Camell; Beshay N. Zordoky (Scientific Reports)
Abstract The long-term effects of doxorubicin (DOX) chemotherapy on thymic immune function in childhood cancer survivors remain inadequately understood. This study explores the immediate and delayed impacts of low-dose DOX on thymic immune populations using a juvenile mouse model. Male mice received intraperitoneal DOX injections (4 mg/kg/week) for three weeks, with evaluations performed at one- and five-weeks post treatment. Thymic samples were collected and analyzed using multi-parameter flow cytometry to assess changes in immune cell composition and phenotype. Additionally, real-time polymerase chain reaction (RT-PCR) was employed to measure gene expression of cytokines and senescence markers. One week after DOX administration, significant thymic atrophy was evident. While mature CD3+CD4+ T-cell frequency remained unchanged, CD3+CD8+ T-cells significantly increased, suggesting differential effects on T-cell subsets. PD1+ expression increased across naïve and memory CD4+ T-cell subsets, suggesting activation or exhaustion. Additionally, Ki67+ expression was elevated in naïve and memory CD8+ T-cells, indicating enhanced proliferation. Gene expression analysis revealed upregulation of Foxn1, Pax1, Ifnγ, and Il7 whereas Il6 and Il17 were downregulated. Furthermore, Cdkn1a (p21 ) expression was elevated, suggesting immune dysregulation and early immunosenescence. At five weeks, thymic weight rebounded; however, T-cell subsets displayed persistent perturbations. Central memory and effector memory CD4+ T-cells were reduced, while naïve CD4+ T-cells showed increased Ki67+ expression. In contrast, CD8+ T-cells subsets remained largely unchanged, except for a decrease in central memory cells. Although expression of thymus-related genes was normalized, p21 expression remained elevated, suggesting lingering immunosenescence. These findings highlight the complex effects of DOX, including acute thymic atrophy due to T-cell depletion, and a delayed recovery with persistent immunosenescence, underscoring the need for strategies to preserve immune function in childhood cancer survivors.